Synthesis and Characterization of pH-Sensitive Inulin Conjugate of Isoniazid for Monocyte-Targeted Delivery - Franklin Afinjuomo; Thomas G. Barclay; Ankit Parikh; Rosa Chung; Yunmei Song; Gayathri Nagalingam; Jamie Triccas; Lixin Wang; Liang Liu; John D. Hayball; Nikolai Petrovsky; Sanjay Garg (MDPI AG, 2019)
The use of particles for monocyte-mediated delivery could be a more efficient strategy and approach to achieve intracellular targeting and delivery of antitubercular drugs to host macrophages. In this study, the potential of inulin microparticles to serve as a drug vehicle in the treatment of chronic tuberculosis using a monocytes-mediated drug targeting approach was evaluated. Isoniazid (INH) was conjugated to inulin via hydrazone linkage in order to obtain a pH-sensitive inulin-INH conjugate. The conjugate was then characterized using proton nuclear magnetic resonance (1HNMR), Fourier transform infrared spectroscopy (FTIR) as well as in vitro, cellular uptake and intracellular Mycobacterium tuberculosis (Mtb) antibacterial efficacy. The acid-labile hydrazone linkage conferred pH sensitivity to the inulin-INH conjugate with ~95, 77 and 65% of the drug released after 5 h at pH 4.5, 5.2, and 6.0 respectively. Cellular uptake studies confirm that RAW 264.7 monocytic cells efficiently internalized the inulin conjugates into endocytic compartments through endocytosis. The intracellular efficacy studies demonstrate that the inulin conjugates possess a dose-dependent targeting effect against Mtb-infected monocytes. This was through efficient internalization and cleavage of the hydrazone bond by the acidic environment of the lysosome, which subsequently released the isoniazid intracellularly to the Mtb reservoir. These results clearly suggest that inulin conjugates can serve as a pH-sensitive intracellular drug delivery system for TB treatment.